2001
DOI: 10.1002/1521-3951(200111)228:1<273::aid-pssb273>3.3.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Study on Temperature Dependence of Band Gap Energy of GaAsN Alloys

Abstract: a), S. Kikuchi (a), Y. Hijikata (a), S. Yoshida (a), D. Aoki (b), and K. Onabe (b)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…. The delocalized exciton transition energy at 0 K naturally decreases with increasing nitrogen concentration, and both a B and Θ B increase with x and continuously lead to the alloy regime studied previously . It is, therefore, found that even dilute alloys follow the same trend as GaAsN alloys with higher nitrogen concentrations of 1–3% , suggesting that electrons distributed around N atoms interact preferentially with the localized Ga–N vibration mode with higher phonon energy.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…. The delocalized exciton transition energy at 0 K naturally decreases with increasing nitrogen concentration, and both a B and Θ B increase with x and continuously lead to the alloy regime studied previously . It is, therefore, found that even dilute alloys follow the same trend as GaAsN alloys with higher nitrogen concentrations of 1–3% , suggesting that electrons distributed around N atoms interact preferentially with the localized Ga–N vibration mode with higher phonon energy.…”
Section: Resultssupporting
confidence: 52%
“…We previously found from the temperature dependence of photoluminescence (PL) spectra of GaAsN alloys that the PL peak energy shift due to the temperature change decreases with increasing nitrogen concentration, which is attributed in part to the influence of the localized‐state emission at lower temperatures . Furthermore, we revealed that the small PL peak energy shift at higher temperatures is due to a decrease in the temperature dependence of the band gap energy.…”
Section: Introductionmentioning
confidence: 76%
“…One of the candidates of poor electron mobility is due to these N related shallow defects [2,3]. "S-shape" behavior in temperature dependence of photoluminescence suggested that there are some shallow level in near-band-edge of GaAsN [4,5]. However, these trap levels were not understood yet.…”
Section: Introductionmentioning
confidence: 99%